Ensemble of point defects in CdTe single crystals and films in the case of full equilibrium and quenching - Kosyak, V.V.; Opanasyuk, A.S.; Protsenko, I.Yu. (Functional Materials, 2005)
The ensemble of point defects in CdTе undoped single crystals has been modeled. Two extreme cases were calculated: full equilibrium and quenching. Dependences of the point defect and free carrier concentrations on technological parameters of growing, post-growth annealing in Cd vapor, and the sample examination temperature have been studied. The growth conditions of single crystals and n- and p-type conductivity CdTе films were defined. The results obtained have been compared with experimental data. This made it possible to make conclusions concerning validity of the studied models and to propose additional experiments to make final choice between them. Проведено моделирование ансамбля точечных дефектов в нелегированных монокристаллах и пленках теллурида кадмия. Расчеты выполнены для двух крайних случаев - полного равновесия и закалки дефектов. Получены зависимости концентрации собственных дефектов, свободных носителей заряда от технологических параметров выращивания, послеростового отжига в парах кадмия и температуры исследования образцов. Определены условия изготовления монокристаллов и пленок CdTе n- и p-типа проводимости. Проведено сравнение полученных результатов с экспериментальными данными, что позволило сделать выводы относительно обоснованности рассмотренных моделей и предложить дополнительные эксперименты, позволяющие сделать окончательный выбор между ними. Проведено моделювання ансамблю точкових дефектiв у нелегованих монокристалах i плiвках телуриду кадмiю. Розрахунки виконано для двох крайнiх випадкiв - повної рiвноваги i загартування дефектiв. Одержано залежностi концентрацiї власних дефектiв, вiльних носiїв заряду вiд технологiчних параметрiв вирощування, пiсляростового вiдпалу у парах кадмiю i температури дослiдження зразкiв. Визначено умови виготовлення монокристалiв i плiвок CdTе n i p-типу провiдностi. Проведено порiвняння отриманих результатiв з експериментальними даними, що дозволило зробити висновки щодо обгрунтованостi розглянутих моделей i запропонувати додатковi експерименти, якi дозволяють зробити остаточний вибiр мiж ними.